2015
DOI: 10.1039/c5ra07557b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced water vapor barrier property of poly(chloro-p-xylylene) film by formation of dense surface cross-linking layer via hyperthermal hydrogen treatment

Abstract: Polymer barrier materials have been increasingly used in many applications such as metal anti-corrosion, electronic packaging, and cultural relic protection, but they have poor resistance to water vapor compared to inorganic barrier materials. Herein, we demonstrate the first application of hyperthermal hydrogen induced cross-linking (HHIC) technology to improve dramatically the water vapor barrier properties of Poly(chloro-p-xylylene) (PPXC) films by building a dense and intact surface cross-linking layer. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The improved barrier property should be attributed to the formed cross-linking layer that can act as a dense barrier layer for blocking water vapor. 43 This result additionally proves that hyperthermal hydrogen projectiles can penetrate the PAA layer to reach the underlying film and subsequently induce the cross-linking of the PPXC film. Overall, the above results suggest that HHIC treatment can successfully cross-linking PAA and form a hydrophilic layer stably bonding to PPXC film without destroying the desired COOH groups from PAA at an optimized treatment time (60 s).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved barrier property should be attributed to the formed cross-linking layer that can act as a dense barrier layer for blocking water vapor. 43 This result additionally proves that hyperthermal hydrogen projectiles can penetrate the PAA layer to reach the underlying film and subsequently induce the cross-linking of the PPXC film. Overall, the above results suggest that HHIC treatment can successfully cross-linking PAA and form a hydrophilic layer stably bonding to PPXC film without destroying the desired COOH groups from PAA at an optimized treatment time (60 s).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides, it is observed that the WVTR of PAA–PPXC film after HHIC treatment obviously decreases from 0.48 to 0.18 g/(m 2 ·day) (as shown in Figure ). The improved barrier property should be attributed to the formed cross-linking layer that can act as a dense barrier layer for blocking water vapor . This result additionally proves that hyperthermal hydrogen projectiles can penetrate the PAA layer to reach the underlying film and subsequently induce the cross-linking of the PPXC film.…”
Section: Resultsmentioning
confidence: 99%
“…Poly( p-xylylene) (PPX) prepared by chemical vapour deposition (CVD) could be an ideal coating material due to its homogeneous and conformal surfaces, good adhesion to other materials, chemical resistance, excellent biocompatibility, and thermal stability. [13][14][15] It can be used for hydrophobic coating for moisture barriers, 16,17 reinforcement of microstructures, 18 and protection materials for plastic, rubber, and metals from a harsh environment. 19,20 In this work, PPX was coated onto the ultralight polymer fibre sponges.…”
Section: Introductionmentioning
confidence: 99%